2007
DOI: 10.1103/physrevd.76.074021
|View full text |Cite
|
Sign up to set email alerts
|

Diquark correlations in baryons on the lattice with overlap quarks

Abstract: We evaluate baryon wave functions in both the Coulomb and Landau gauge in lattice QCD. These are constructed from quark propagators calculated with the overlap Dirac operator on quenched gauge configurations at β = 6. By comparing baryon states that differ in their diquark content, we find evidence for enhanced correlation in the scalar diquark channel, as favored by quark models. We also summarize earlier results for diquark masses in the Landau gauge, casting them in a form more easily compared with subseque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 32 publications
3
84
0
Order By: Relevance
“…There is, however, an indication that the overlap fermion formulation has relatively small scaling violation within the quenched calculation of B K [38], where no significant dependence on the lattice spacing was observed between 1/a ∼ 2.2 GeV and 1.5 GeV. Even at a fixed lattice spacing, the use of a different input to fix the lattice spacing could lead to an appreciable change of B K because B K has a significant dependence on the squared meson mass (am 12 ) 2 as seen in Fig.…”
Section: Other Systematic Errorsmentioning
confidence: 99%
“…There is, however, an indication that the overlap fermion formulation has relatively small scaling violation within the quenched calculation of B K [38], where no significant dependence on the lattice spacing was observed between 1/a ∼ 2.2 GeV and 1.5 GeV. Even at a fixed lattice spacing, the use of a different input to fix the lattice spacing could lead to an appreciable change of B K because B K has a significant dependence on the squared meson mass (am 12 ) 2 as seen in Fig.…”
Section: Other Systematic Errorsmentioning
confidence: 99%
“…In [13] and [14] ratios were suggested that give directly the BSM to SM contribution at the physical point,…”
Section: Measurement Typesmentioning
confidence: 99%
“…While string-type models consisting of a quark plus a diquark have been studied using various analytic techniques (see [2] for a review), there have only been a few studies of this type of system on the lattice. These studies have investigated the mass of diquarks [3][4][5][6][7], and, more recently, the nature of diquark correlations [8]. Recently we investigated the formation of flux tubes in static baryon systems on the lattice using a high statistics approach which enabled us to observe correlations between the vacuum action density and the quark positions in a gauge independent manner [9].…”
Section: Introductionmentioning
confidence: 99%